Expanding the applicability of cytochrome P450s and other haemoproteins. (December 2020) - Ariyasu, Shinya; Stanfield, Joshua Kyle; Aiba, Yuichiro; Shoji, Osami
Abstract: Cytochrome P450BM3 has long been regarded as a promising candidate for use as a biocatalyst, owing to its excellent efficiency for the hydroxylation of unactivated C–H bonds. However, because of its high substrate specificity, its possible applications have been severely limited. Consequently, various approaches have been proposed to overcome the enzyme's natural limitations, thereby expanding its substrate scope to encompass non-native substrates, evoking chemoselectivity, regioselectivity and stereoselectivity and enabling previously inaccessible chemical conversions. Herein, these approaches will be classified into three categories: (1) mutagenesis including directed evolution, (2) haem substitution with artificial cofactors and (3) use of substrate mimics, 'decoy molecules'. Herein, we highlight the representative work that has been conducted in above three categories for discussion of the future outlook of P450BM3 in green chemistry.